Impacts of COVID-19 on refugees and immigrants in the United States: A call for action. (September 2021) - Rafieifar, Maryam; Naseh, Mitra; Potocky, Miriam; Zajicek-Farber, Michaela L; Kim, Wooksoo; Padilla, Beatriz; Reina Ortiz, Miguel; Lopez, Jasiel A
The COVID-19 crisis has increasingly exerted a disproportionate impact on the lives of migrant populations. A group of interdisciplinary migration experts convened a round table in June 2020, to discuss the numerous challenges faced by immigrants, refugees, and migrants in the United States. The discussion revealed many social inequities, including insufficient financial and social resources, non-existent or minimal health supports, lack of or inadequate access to community supports, and social and racial discrimination, among other difficulties. To promote social justice and encourage research, the ensuing essay is a call for action to stimulate and build knowledge about social work and public health issues as they relate to the needs of immigrants, refugees, and migrant populations in the United States during the COVID-19 pandemic.